PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI - Alvindo Oktovian; Meiffa Herfianti (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to examine the influence of brand image and product quality on consumers’ purchase intention of iPhone at Pstore Bengkulu City. This research employed a quantitative survey method involving 150 respondents who directly visited the store. Data were analyzed using multiple linear regression with SPSS version 25. The instrument testing results indicated that all questionnaire items were valid (r-count > 0.381) and reliable, with Cronbach’s Alpha values of 0.852 for brand image, 0.739 for product quality, and 0.915 for purchase intention (α > 0.60). Hypothesis testing results revealed that brand image has a positive and significant effect on purchase intention, product quality also has a positive and significant effect on purchase intention, and simultaneously both variables significantly influence consumers’ purchase intention at a 0.05 significance level. Keywords: Brand Image, Product Quality, Purchase Intention